Cherubino's leap in search of the Enlightenment moment - Kramer, Richard 1938- (The University of Chicago Press, 2016)
For the Enlightenment mind, from Moses Mendelssohn's focus on the moment of surprise at the heart of the work of art to Herder's imagining of the seismic moment at which language was discovered, it is the flash of recognition that nails the essence of the work, the blink of an eye in which one's world changes. In "Cherubino's Leap", Richard Kramer unmasks such prismatic moments in a range of iconic instrumental works by Emanuel Bach, Haydn, and Mozart; in the musical engagement with the formidable odes of Friedrich Klopstock; and, on the grand stage of opera, at the intense moment of recognition in Gluck's "Iphigenie en Tauride" and the exquisitely introverted phrase that complicates Cherubino's daring escape in Mozart's Figaro. Finally, the tears of the disconsolate Konstanze in Mozart's "Die Entführung aus dem Serail" inspire a reflection on the tragic aspect of the composer's operatic women. Other players from literature and the arts Diderot, Goethe, Lessing among them enrich the landscape of this journey through the Enlightenment imagination. - Richard Kramer is distinguished professor emeritus of music at the CUNY Graduate Center. A fellow of the American Academy of Arts and Sciences, he is the author of the award-winning Distant Cycles: Schubert and the Conceiving of Song, also published by the University of Chicago Press, and Unfinished Music.